2020
DOI: 10.1590/0001-3765202020190161
|View full text |Cite
|
Sign up to set email alerts
|

Lecithochirium monticellii digenetic trematode parasites of Trichiurus lepturus (Actinopterygii) from the state of Rio de Janeiro, Brazil, with notes on its taxonomy

Abstract: Trichiurus lepturus (Actinopterygii, Perciformes) is a commercially and economically important fish. A total of 60 specimens of this cutlassfish were collected of the coast the municipalities of Niterói and Cabo Frio, state of Rio de Janeiro, Brazil. The fish were measured, necropsied, filleted and had their organs investigated for digenetic trematodes. Taxonomic identification was based on morphological and morphometric characters. The specimens of T. lepturus were parasitized with adult specimens of Lecithoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
4
4
0
Order By: Relevance
“…The morphology and morphometry of the specimens of L. monticellii collected in the present study were in accordance with the original description (Linton, 1940) and redescriptions (Skrjabin & Guschanskaja, 1955;Nasir & Díaz, 1971;Fernandes et al, 1985;França et al, 2020) of the species. Morphometrically, the present specimens were smaller than those collected from Trichiurus lepturus L. from off the coast of Cumaná, State of Sucre, Venezuela (Nasir & Díaz 1971), and from Trachurus lathami Nichols, 1920 and T. lepturus from off the coast of the state of Rio de Janeiro, Brazil (Fernandes et al, 1985;França et al, 2020), which can be considered intraspecific variation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The morphology and morphometry of the specimens of L. monticellii collected in the present study were in accordance with the original description (Linton, 1940) and redescriptions (Skrjabin & Guschanskaja, 1955;Nasir & Díaz, 1971;Fernandes et al, 1985;França et al, 2020) of the species. Morphometrically, the present specimens were smaller than those collected from Trichiurus lepturus L. from off the coast of Cumaná, State of Sucre, Venezuela (Nasir & Díaz 1971), and from Trachurus lathami Nichols, 1920 and T. lepturus from off the coast of the state of Rio de Janeiro, Brazil (Fernandes et al, 1985;França et al, 2020), which can be considered intraspecific variation.…”
Section: Discussionsupporting
confidence: 86%
“…Alarcos & Timi (2012) studied the same three species of flounders as the present study in Argentina and found L. microstomum [=L. monticellii, as suggested by França et al (2020)] only parasitizing X. rasile. Alarcos et al (2016) reported this digenean species parasitizing P. isosceles from off the state of Rio de Janeiro.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our single specimen closely resembles L. monticellii collected from the stomach of T. lepturus in the Atlantic Ocean, Rio de Janeiro, Brazil, by França et al [ 15 ], in that it possesses a genital pore at or slightly posterior to the pharynx, a tripartite seminal vesicle, and testes being separated from the ventral sucker. In comparison with large specimens collected by França et al [ 15 ], our specimen differs by having a wider body (694 vs. 220–520), a longer sinus-sac (179 vs. 50–100), a slightly larger sucker ratio (1:2.46 vs. 1:1.95–2.41), and shorter eggs (11–15 × 9–11 vs. 23–28 × 9–12).…”
Section: Resultssupporting
confidence: 64%
“…A total of 28 species from 10 genera are known to parasitise fishes from 28 families of 17 orders in Brazil [ 7 , 9 ]. The majority of species were reported from fishes of the family Carangidae (Carangiformes) collected off the Rio de Janeiro coast [ 9 , 15 , 16 ]. Only recently were the first DNA sequences of Brazilian marine digenean trematodes published, with three of them being of hemiurids [ 7 ].…”
Section: Introductionmentioning
confidence: 99%